The cause of acute lethality of mice exposed to a laser-induced shock wave to the brainstem - Koji Yamamura; Nobuaki Kiriu; Satoshi Tomura; Satoko Kawauchi; Kaoru Murakami; Shunichi Sato; Daizoh Saitoh; Hidetaka Yokoe (Scientific Reports, 2022)
Abstract Air embolism is generally considered the most common cause of death within 1 h of a blast injury. Shock lung, respiratory arrest, and circulatory failure caused by vagal reflexes contribute to fatal injuries that lead to immediate death; however, informative mechanistic data are insufficient. Here we used a laser-induced shock wave (LISW) to determine the mechanism of acute fatalities associated with blast injuries. We applied the LISW to the forehead, upper neck, and thoracic dorsum of mice and examined their vital signs. Moreover, the LISW method is well suited for creating site-specific damage. Here we show that only mice with upper neck exposure, without damage elsewhere, died more frequently compared with the other injured groups. The peripheral oxygen saturation (SpO2) of the former mice significantly decreased for < 1 min [p < 0.05] but improved within 3 min. The LISW exposure to the upper neck region was the most lethal factor, affecting the respiratory function. Protecting the upper neck region may reduce fatalities that are related to blast injuries.